Family Resilience, Parenting Styles and Psychosocial Adjustment of Children With Chronic Illness: A Cross-Sectional Study - Qiu, Yuan; Xu, Liuqing; Pan, Yinzhu; He, Chunlei; Huang, Yingying; Xu, Huan; Lu, Zhongqiu; Dong, Chaoqun (Frontiers in Psychiatry, 2021)
Objectives: To evaluate the level of parent-reported family resilience, parenting styles and psychosocial adjustment of children with chronic illness and to identify the relationships between family resilience, parenting styles and psychosocial adjustment in families with children with chronic illness. Methods: A cross-sectional study was conducted between June 2019 and August 2019. A total of 236 parents of children with chronic illness and 98 parents with healthy children were recruited from general hospitals by convenience sampling. A parent completed the Chinese Family Resilience Assessment Scale, the Parenting Rearing Patterns Questionnaire and the Strengths and Difficulties Questionnaire. Family resilience, parenting styles, and psychosocial adjustment of children with chronic illness were compared with those of healthy children. Structural Equation Modeling (SEM) was performed to explore the mediation effect of parenting styles between family resilience and psychosocial adjustment among children with chronic illness. Results: Parents of children with chronic illness reported lower level of family resilience and authoritative parenting, but more peer relationship problems compared to parents of healthy children. SEM showed that authoritative parenting fully mediated the relationship between family resilience and psychosocial adjustment of children with chronic illness. Conclusion: Childhood chronic illness reduces family resilience, authoritative parenting and children’s psychosocial adjustment, but authoritative parenting mediated these effects, so authoritative parenting may be important for family resilience in families of children with chronic illness. Pediatric clinicians and nurses should provide family-centered interventions, as well as parenting training, to improve children’s psychosocial outcomes.